HYDROTHERMAL LIQUEFACTION OF BLACK LIQUOR INTO PLATFORM CHEMICALS - Mansur, Dieni; Simanungkalit, Sabar Pangihutan; Rinaldi, Nino; Abimanyu, Haznan (LIPI Press, 2016)
Currently, much attention is devoted to produce bioethanol based on lignocellulosic materials for alternativefuels. Production of bioethanol from lignocellulosic generates black liquor as a waste during the pretreatmentprocess. The black liquor has a potential to produce platform chemicals. Conversion of black liquor into platformchemicals was carried out by hydrothermal liquefaction by involving water as reaction medium at 200275 C.Through the hydrothermal process combined with water at high temperature, catalytic role could be taken over bysodium sulfate. Increase in temperature up to 275C, activity of water combined with sodium sulfate also increasedin decomposition of block chemicals containing in the black liquor. The black liquor was converted into oxygenatedcompounds, such asphenol, propylene oxide, butyrolactone, and quaiacol. The chemicals were recovered as23, 16, 11 and 8 mol%, respectively.